EFFET DE L’ASSOCIATION DE DIFFÉRENTS CULTIVARS DE BANANIERS (MUSA SPP.) TOLÉRANTS SUR L’INCIDENCE DE LA CERCOSPORIOSE NOIRE CHEZ LE CULTIVAR SENSIBLE "ORISHELE" EN CÔTE D’IVOIRE - Seydou, Tuo; Elisée, Amari Ler-N’ogn Dadé Georges; Brahima, Camara; Martial, Kassi Fernand; Léonard, Ouédraogo Somgnogdin; Siaka, Traoré; Jean-Paul, Lorng; Emmanuel, Kouakou Amani; Daouda, Koné (European Scientific Journal, ESJ, 2015)
The cultivation of bananas in the classical systems by smallholders is seriously threatened by the Black Leaf Streak Disease (BLSD). The chemical and genetic fight methods against this disease showed some limitations and disadvantages. That suggests the possibility of the efficient use of susceptible banana in combination of tolerant hybrids as fight methods. This study is carried out to assess the performances of various prototypes or associations of banana on the control of BLSD. These protocols can reduce pest pressure in banana farm and increase the yield of the cultivar "Orishele" which is susceptible to BLSD. During eight months of vegetative growth, the varietal association prototypes of banana had shown variable effectiveness face the disease according to the pathological descriptors. "Orishele" cultivar in association plots showed high tolerance level against BLSD than those of non-association plots. In the prototype with a low density of the cultivar "Orishele", the severity indices of the disease were low. When "Orishele" was associated with the tolerant hybrid PITA 3 or the variety "Figue Sucrée", the severity indices were respectively 10.99 % and 11.07 %.When "Orishele" is on non-association plots the severity indices was high (33.47 %). Banana cultivation in combination of susceptible and tolerant varieties in almost equal proportions seems an ideal strategy to slow the spread of the fungus causing BLSD and provide better yield at harvest of susceptible cultivars to the BSD.